The Pathogenesis of Lupus Nephritis - Lech, Maciej (American Society of Nephrology, 2013)
Lupus nephritis is an immune complex GN that develops as a frequent complication of SLE. The pathogenesis of lupus nephritis involves a variety of pathogenic mechanisms. The extrarenal etiology of systemic lupus is based on multiple combinations of genetic variants that compromise those mechanisms normally assuring immune tolerance to nuclear autoantigens. This loss of tolerance becomes clinically detectable by the presence of antinuclear antibodies. In addition, nucleic acids released from netting or apoptotic neutrophils activate innate and adaptive immunity via viral nucleic acid-specific Toll-like receptors. Therefore, many clinical manifestations of systemic lupus resemble those of viral infection. In lupus, endogenous nuclear particles trigger IFN-α signaling just like viral particles during viral infection. As such, dendritic cells, T helper cells, B cells, and plasma cells all contribute to the aberrant polyclonal autoimmunity. The intrarenal etiology of lupus nephritis involves antibody binding to multiple intrarenal autoantigens rather than the deposition of circulating immune complexes. Tertiary lymphoid tissue formation and local antibody production add to intrarenal complement activation as renal immunopathology progresses. Here we provide an update on the pathogenic mechanisms that lead to lupus nephritis and provide the rationale for the latest and novel treatment strategies.